NEGOTIATING IDENTITY UNDER THE CULTURAL SUPEREGO IN ON EARTH WE’RE BRIEFLY GORGEOUS - Indra Cahyo Nugroho; Thohiriyah (English Literature Department, Faculty of Economics, Law, and Humanities, 2026)
Diasporic individuals often face complex identity formation that involves psychological tension driven by conflicting cultural moralities. In Ocean Vuong’s On Earth We’re Briefly Gorgeous, this tension is illustrated through the protagonist, Little Dog, whose identity is shaped by familial obligations, cultural expectations, and social marginalization. This study aims to explore how the cultural superego influences Little Dog’s identity formation and how he navigates cultural pressures within a Vietnamese-American diaspora context. Using a qualitative descriptive method, this research draws on Freudian psychoanalysis, particularly Freud’s concept of the cultural superego. The data consists of selected narrative passages, dialogues, and character reflections that expose themes of moral regulation, guilt, repression, and cultural pressure. The analysis employs thematic textual analysis to interpret how internalized cultural authority influences identity negotiation. The findings suggest that the cultural superego functions through various mechanisms, including familial duty, guilt, social discrimination, norms of masculinity, and the cultural gaps between Vietnamese and American values. These mechanisms act as internal moral regulators, shaping desires, emotional expressions, and self-perception. As a result, identity is recognized as a continuous negotiation rather than a stable construct. This study contributes to psychoanalytic literary studies by demonstrating how Freud’s concept of the cultural superego can be applied to diasporic literature. It explains identity formation as a psychologically regulated process influenced by collective moral authority rather than solely by individual autonomy.